Glee and New Directions for Social Change
XVI, 232 p.
Keywords: In the fall of 2009, the Fox network took a bold step in their primetime television lineup. Borrowing from the success of reality music performance shows like its own American Idol, the network introduced us to the students at McKinley High School, a fictional high school in Lima, OH, and home to the glee club known as the New Directions. The group is made up of freaks and geeks who feel the wrath of being “different.” The cool kids are hell bent on making life difficult for the students in glee club. Yet, because of the determination of Mr. Will Schuester, the club’s advisor, along with a few great songs, Glee has brought a new tone of inclusion to modern television and direct parallels can be seen between the experiences of the show choir members and what is happening in contemporary society. Glee has shown the importance of examining the intersections of pop culture and social issues; this text will encourage thinking on how effective the show has been beyond the screen. Essays provide critical analyses of the show, its characters, and its overall usefulness as a commentary on social issues. The show’s content often deals with subject matter that would lend easily to critique around such social issues as sexuality, bullying, interpersonal communication, conflict resolution, and family relationships. This text invites readers to examine the intersections between media, society, and the individual.